Implementation of Practical Accounting Through Daily Journal Recording by Students at Sangkhom Islam Wittaya School, Thailand - Mukminati, Mukminati; Mangngalla, Muliani; K, M. Yusuf; HA, Sitti Jami’ah; Darmawan, Wawan (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2025)
This Community Service Program aims to improve students' accounting literacy through the activity “Implementation of Practical Accounting Through Daily Journal Recording” at Sangkhom IslamWittaya School, Thailand. The background of this activity is the low level of students' understanding of accounting, which is considered difficult and abstract, so a simple, fun, and applicable learning method is needed. The learning by doing approach is used so that students can directly practice recording simple transactions based on their daily activities, such as receiving pocket money, buying necessities, or borrowing items. The activity was carried out in stages: pre-activity (needs analysis, material preparation, and coordination with the school), core activity (introduction to accounting concepts and daily journal entry practice), and post-activity (evaluation through pre-tests and post-tests). The results of the activity showed a significant improvement in student understanding, as seen from the increase in the average scores on five assessment indicators, namely understanding of basic accounting concepts, identification of simple transactions, journal entry skills, recording discipline, and summary writing skills. In addition to improving cognitive aspects, this activity also fostered discipline, responsibility, and accuracy in students' daily financial management. With teacher involvement, this program has the potential to be sustainable and can be used as a model for basic accounting learning in other schools. Contribution to Sustainable Development Goals (SDGs):SDG 4: Quality EducationSDG 8: Decent Work and Economic GrowthSDG 11: Sustainable Cities and CommunitiesSDG 12: Responsible Consumption and Production